QTL analysis and management of plant productivity in the precision agriculture - Yu. V. Chesnokov (Овощи России)
Modern crop cultivation technologies have reached the limits of “saturation” both in the ecological (environmental pollution, suppression of the mechanisms of its self-regulation), energy (exponential growth of irreplaceable energy costs for each additional unit of production), and in production. In this regard, environmental factors (air drought, frosts, active temperatures, etc.), which cannot be optimized, are becoming increasingly important in ensuring a steady increase in the yield of cultivated plant forms. In recent decades, more and more attention has been paid to technogenic and biological systems of agriculture, based on the ecologization and biologization of the intensification processes of adaptive crop production. Such approaches are the precision agriculture system (PA) and QTL analysis. Using these approaches allows not only to ensure a steady increase in productivity due to the combined use of the advantages of precision farming and molecular genetic assessment, including the creation of new forms and varieties that are responsive to РА agricultural practices, but also to level the negative impact of abiotic and biotic environmental factors that limit the size and quality of the crop as well as plant productivity. It is shown that the strategy of adaptive intensification of crop production through the use of the TK system and QTL analysis approaches is not alternative to existing farming systems, however, it focuses modern agriculture on the growth of knowledge-intensive agricultural production as a whole. An analysis of the causes under consideration, the current unfavorable trends in modern crop production and agriculture, clearly shows their scale and long-term nature, and therefore the inevitability of the search for new priorities for intensification of crop production and agriculture, providing a qualitatively new stage of their development in the interests of man.